2021
DOI: 10.3389/fneur.2021.780624
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography to Assess Neurodegeneration in Phenylalanine Hydroxylase Deficiency

Abstract: In phenylalanine hydroxylase (PAH) deficiency, an easily feasible method to access the progression of neurodegeneration is warranted to contribute to current discussions on treatment indications and targets. The objective of the present study was to investigate whether optical coherence tomography (OCT) measures as markers of neurodegeneration differ between patients with PAH deficiency and healthy controls (HCs) according to phenotype and metabolic control. In this single-center cross-sectional study, 92 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…The patients examined in this study were part of a previously published cohort of PKU patients studied with OCT ( 35 ). The pRNFL thickness and GCIPL and INL volumes of the ETPKU patients in this study are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The patients examined in this study were part of a previously published cohort of PKU patients studied with OCT ( 35 ). The pRNFL thickness and GCIPL and INL volumes of the ETPKU patients in this study are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Limited data were available only for patients who were treated at other metabolic centers in childhood ( N = 1), or had poor adherence in adolescence ( N = 2) or adulthood ( N = 1). Indices of Phe control based on dried blood spot measurement were calculated as described before ( 16 , 35 , 49 , 50 ). We averaged Phe control in the following age bands: childhood 0–10 years of age, adolescence 11–16 years of age, adulthood 17 years of age to present, and lifetime.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tetrahydrobiopterin (BH 4 , prescribed as sapropterin dihydrochloride) is a pharmacological treatment option that aims to further improve outcomes by increasing residual PAH activity in a subset of PKU patients. Through this mechanism, daily administration of BH 4 in BH 4 -responsive patients may result in lower blood Phe concentrations, and possibly in the increased stability of blood Phe concentrations and/or increased dietary Phe tolerance [7][8][9][10][11]. In BH 4 -responsive patients with suboptimal blood Phe concentrations, BH 4 can thus be used to improve metabolic control.…”
Section: Introductionmentioning
confidence: 99%